Application of Emergency Unit Information Systems to Support Hospital Management Systems - Rohmadi Rohmadi; Dwi Iskandar (Institut Teknologi Bisnis AAS Indonesia, 2023)
The development of technology, especially information technology has penetrated into all fields, one of which is the field of health services. By using information technology, data can be processed more quickly, easily and safely so that services can be provided to the community better and more efficiently. Hospitals as one of the providers of health services for the community, have an obligation to provide quality and affordable health services. The methodology in this study starts from analysis, design, coding, support and test. In the analysis stage an analysis is carried out around non-functional requirements and functional requirements, the design stage includes interface design, table design. The next stage is coding, support and test. The conclusions that can be drawn include that the information system can be implemented properly, before being implemented the system has been tested, the information system can provide good data services to patients, the information system can provide good information regarding action reports and visit reports.